Suggestions from the field for return to sports participation following anterior cruciate ligament reconstruction: Soccer - Bizzini, M.; Hancock, D.; Impellizzeri, F. (Journal of Orthopaedic & Sports Physical Therapy, 2012)
Successful return to play remains a challenge for a soccer player after anterior cruciate ligament reconstruction. In addition to a successful surgical intervention, a soccer-specific functional rehabilitation program is essential to achieve this goal. Soccer-like elements should be incorporated in the early stages of rehabilitation to provide neuromuscular training specific to the needs of the player. Gym-based and, later, field-based drills are gradually intensified and progressed until the player demonstrates the ability to return to team practice. In addition to the recovery of basic attributes such as mobility, flexibility, strength, and agility, the surgically repaired knee must also regain soccer-specific neuromuscular control and conditioning for an effective return to sports. The individual coaching of the player by the sports physiotherapist and compliance with the training program by the player are key factors in the rehabilitation process. To minimize reinjury risk and to maximize the player`s career, concepts of soccer-specific injury prevention programs should be incorporated into the training routine during and after the rehabilitation of players post-ACL reconstruction